Analysis Morphological Character and Relationship of Suweg (Amorphophallus campanulatus) Plant in Jombang District - Muhammad Ega Saputro; Umi Kulsum Nur Qomariah; Mazidatul Faizah (AGARICUS: Advances Agriculture Science & Farming, 2022)
Suweg is one of the tuber-producing plants in Jombang. Suweg plants in Jombang have not been cultivated regularly, but actually, suweg tubers have great potential to be used as food diversification material in the future. The development of suweg plants, for example assembling varieties has not been done much. The first step in assembling varieties that must be done is germplasm exploration. This study aims to obtain information on the suweg plant in Jombang, to find out the differences in plant characteristics and the kinship relationship of the suweg plant in the same sub-district or in different sub-districts. The research was carried out in Jombang district, covering the Districts of Wonosalam, Kesamben, Ngusikan, Together, Kudu and Plandaan. The location selection is determined based on the results of the preliminary survey. The research was conducted from April to June 2020. The data analysis used a descriptive method, namely simplifying and organizing the data to obtain an overall picture of the object being observed. In addition to the use of descriptive analysis, kinship analysis was carried out using cluster data analysis. In the kinship analysis, the similarity matrix was calculated manually, while the dendrogram was made using NTSys software. The results obtained 9 plant samples from 6 locations. Two samples from Wonosalam location 1 and Wonosalam location 2 , One sample from Kesamben location 1 , One sample from Ngusikan location 1 , Three samples from joint location 1 , Together with location 2 , Together with location 3 , One sample from Kudu location 1 and one sample from Location plan 1 . Kinship analysis showed various relationships with a similarity matrix value of 0.52 – 1.00, this indicates that the diversity of suweg plants in Jombang is very high.